Intimate Partner Violence in the Sub-Saharan African Immigrant Community in Chicago: A Changing Landscape - Kathryn Wenham; Bernadette Sebar; Patricia Lee; Neil Harris; Gabrielle Campbell (MDPI AG, 2022)
The challenges of conducting research on intimate partner violence (IPV) in immigrant communities means little is known about the occurrence of various forms of IPV, making it difficult to address in these populations. This research draws on data gathered in Chicago's large and varied African immigrant communities. This research used a mixed methods approach: collection of quantitative survey data on occurrence, followed by qualitative interviews to explain the results. Missing quantitative data and contradicting qualitative responses made it difficult to draw definite conclusions on physical IPV; however, verbal abuse and controlling behaviours appear to be relatively widespread and normalised, and not always viewed as violence. Particularly with the probability of future pandemics and natural disasters, which are known to increase prevalence, it is important to raise awareness of less visible controlling behaviours and verbal abuse as forms of violence, and to implement appropriate prevention programs to minimise a concomitant rise in IPV within African immigrant communities.